Two Scope Portals in Simple Acromioclavicular Joint Type III Injury - Valentina Rossi, M.D.; Claudia Carbone, M.D.; Martina Coppola, M.D.; Gaetano Scognamiglio, M.D.; Gennaro Fiorentino, M.D.; Antonio Allocca, M.D. (Arthroscopy Techniques, 2025)
Acromioclavicular joint dislocation, particularly Rockwood type III, is a common injury and a topic of ongoing debate regarding surgical treatment options. Numerous surgical techniques have been proposed, but it is crucial to focus on methods that minimize invasiveness and promote faster clinical and functional recovery. This article presents an arthroscopic technique for repairing the dislocation using only 2 arthroscopic portals. The approach emphasizes reducing the complexity of the procedure while ensuring efficient results. Additionally, the article analyzes the benefits of this minimally invasive method, including its reproducibility, offering valuable insights for orthopaedic surgeons aiming to refine their techniques.